ROBUST ESTIMATION OF STATIONARY PROCESS - Petrov, Nickolay; Pehlivanova, Tania (International Journal of Computing, 2014)
The use of microprocessor measurement system gives the opportunity to improve the precision of the measurements. It is possible by realization of algorithms, taking in to account the changing conditions of measurement experiment. In the paper it is suggested an adaptive algorithm for calculation of the mathematical expectation MX in the conditions of insufficient knowledge about the interval of correlation.